Mapping the Local Own Resources (PAD) Performance and Regional Dependence in Indonesia 2008-2014: Quadrant Method Approach - Haryanto, Joko Tri (Research and Development Agency Ministry of Home Affairs, 2017)
Fiscal decentralization reform era started since January 1st, 2001, with the implications of changes from centralized to highly decentralized. Unfortunately, it led to a greater dependence on the Local Government to Central Government through the Intergovernmental Transfers, especially on General Allocation Fund (DAU) and also a few on the Specific Allocation Fund (DAK) and Revenue Sharing (DBH). Based on that problem, this research aims to describe regional performances since 2008 until 2014, using several indicators and quadrant method approaches. In accordance with the calculation of the ratio of local independence, the majority of regions are in the category of less independent. While using dependency ratio, the majority of regions are in the group of very large dependency and a dependency. From the results of quadrant analysis methods, most regions are in quadrant III, which means to have a high dependence on government assistance. As a policy recommendation, the government needs to evaluate the improvement of the fiscal decentralization in Indonesia.